THE EMPOWERING PATH: EXPLORING THE MEDIATING ROLE OF ENTREPRENEURSHIP IN THE RELATIONSHIP BETWEEN FINANCIAL MANAGEMENT SKILLS, GROUP IDENTITY, AND WOMEN’S EMPOWERMENT IN RURAL AREAS - Suhailah Kassim; Ahmad Syahmi Ahmad Fadzil; Idris Osman; Mohd Zailani Othman (International Journal of Accounting, Finance and Business, 2023)
This conceptual study examines how financial management skills and group identification affect rural women's empowerment, with a focus on entrepreneurship as a mediator. In rural communities with gender inequities and limited possibilities, women's empowerment is essential to social and economic growth. This study provides a conceptual framework that shows how financial management skills, group identification, entrepreneurship, and rural women's empowerment are interconnected. Financial management skills help women manage their money, make smart decisions, and succeed in business. Group identity gives rural women a sense of belonging, support networks, and the strength to overcome problems and pursue entrepreneurial opportunities. Entrepreneurship helps women leverage their skills and identity, empowering them, according to the framework. This conceptual study adds to the literature by integrating financial management skills, group identification, entrepreneurship, and rural women's empowerment. Empirical research is needed to confirm and examine these links, enabling focused interventions and policies to empower women and advance rural socioeconomic development.